Sheltered bodies:|Investigating the representations of Syrian refugees in Turkish media - Mamak, Onur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study investigates the representations of refugees from the Syrian Civil War in Turkish print media. It does so by quantitatively and qualitatively analyzing all of the refugee related news ran by five newspapers (BirGün, Hürriyet, Sabah, Star, and Yeniçağ) between April of 2014 and March of 2015. Through an in-depth analysis of the legal framework of asylum in Turkey and its political oppositions, these representational strategies are contextualized within the existing refugee regime and its critiques in order to distinguish the practical aims towards which these strategies were mobilized. While the refugees are often conceptualized as a coherent social category both by policy makers and researchers, newspapers consistently rely on already existing ethnoreligious identities in order to represent the refugees and differentiate between them. This thesis aims to uncover the implications of this reliance in both discursive and political contexts.
Keywords: Refugees -- Syria.; Mass media -- Turkey.